Influence of Celebrity Endorsers and Brands Image of Repurchase Intention is mediated by Product Quality of Scarlett Indonesia - Amalia, Rizki (Kirana Publisher (KNPub), 2023)
This research was conducted to find out how the influence exerted by Celebrity endorsements and brands Image on the intensity of repurchasing, through mediation by Product Quality at Brand Scarlett Indonesia. Currently, Celebrity Endorsers are considered more able to attract customers, especially at the age of teenagers and adults. This is due to the rise of social media platforms which are currently more loved by the public than print media or digital media such as radio and television. By conducting the PLS-SEM test on 100 teenagers who have known and or used Scarlett's products at least 1 time, it was found that product quality can mediate the influence of celebrity. Endorsement of Repurchase Intention , while the mediating role of Product Quality on Brand influence Image for Repurchase Intention not found. Celebrities Endorsement has no direct effect on Repurchase Intention , while Brand Image and Product Quality have a significant positive effect on Repurchase Intention .